An interdisciplinary approach for the closure of midline diastema using esthetic buttons (Indian Journal of Case Reports, 2025)
This case report intended to evaluate the clinical outcome of the esthetic buttons for midline diastema space closure rather than full conventional fixed appliance therapy followed by conventional frenectomy. Four esthetic buttons were placed on the central incisors (2 on each tooth) for complete bodily movement of the teeth followed by traction. Space closure was achieved by a 1-month time interval followed by a build-up of lateral incisors and followed by frenectomy. This approach can be followed in patients with compromised financial support who are seeking orthodontic treatment for minor correction and with compromised periodontal support as this delivers less force with great comfort. Patients who are hesitant to begin treatment due to financial obstacles with fixed appliance therapy may find this helpful.